Gas sensing properties of platinum derivatives of single-walled carbon nanotubes: A DFT analysis - P. Pannopard (2018)
The limitations of intrinsic carbon nanotube (CNT) based devices to examine toxic gases motivate us to investigate novel sensors which can possibly overcome sensitivity problems. Pt-CNT assemblies (with Pt deposited externally as well as internally Pt-doped ones) interacting with NO2and NH3are studied and compared with unmodified CNTs. DFT calculations show that Pt can enhance adsorption and charge transfer processes to a very large degree. Incoming gas molecules cause changes in the electronic structure and charge distribution of the Pt-substituted CNTs that are both larger and more far-reaching than in their unmodified counterparts. Their relatively high stability is unaffected by the complexation with NO2and NH3. CNTs with defective surface were also investigated. The sensing performance of Pt-doped CNT is found to be superior to defected CNTs. © 2009 Elsevier Inc. All rights reserved.